Effect of watergym in knee osteoarthritis - Fernandes Guerreiro, Joao Paulo [UNESP]; Turin Claro, Renan Floret [UNESP]; Rodrigues, Joao Daniel [UNESP]; Freire, Beatriz Funayama Alvarenga [UNESP] (Atha Comunicacao & Editora, 2014)
Objective: Evaluate the effectiveness of watergym to alleviate knee osteoarthritis (OA) symptoms and improve locomotor function. Methods: Forty-two volunteers, 38 women and four men with OA, practicing watergym, divided into the following groups: beginners, intermediate, advanced, and advanced level with other physical activities in addition to watergym were included in the study. Individuals were assessed at times zero, 8 and 12 weeks, with classes lasting 45 minutes, twice a week. Function was assessed by the Aggregate Locomotor Function (ALF) score, and pain and other symptoms by the visual analogical scale (VAS) and by the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) questionnaire. Statistical analysis was carried out by the variance analysis for repeated measurements, followed by Tukey's method for comparison of time point means whenever required. Results: None of the tests showed a significant improvement of pain or locomotion. Conclusion: Watergym was not effective in improving symptoms and did not affect the locomotor capacity of individuals with knee OA.
Keywords: Hydrotherapy; Osteoarthritis; Knee; Motor Activity